Organoleptic, Physical And Chemical Characteristics Of Edible Gelatin-Chitosan-Ginger Film - Kalaka, Sri Rahayu; Naiu, Asri Silvana; Husain, Rahim (Jambura Fish Processing Journal, 2022)
The purpose of this study was to examine the quality of edible film packaging based on gelatinchitoson-ginger. The treatment in this study was the use of different gelatins (0.5g, 1g and 1.5g). Parameters tested include hedonic organoleptic testing (taste, texture and aroma), thickness and solubility. The research was analyzed using descriptive method. The results showed that the edible film formula A had the criteria of tasteless, difficult to dissolve, very elastic texture, slightly sour smell, 0.0202mm thickness and 29.10% solubility. Edible film formula B has the criteria of tasteless, easily soluble, elastic texture, slightly sour smell, 0.0272mm thickness and solubility: 37.13%. Edible film formula C has the criteria of tasteless, easy to dissolve, fairly elastic texture, 0.0293mm thickness and solubility: 39.90%.